A Phase 2 Study of Oxaliplatin Combined With Continuous Infusion Topotecan for Patients With Previously Treated Ovarian Cancer. Issue 9 (1st November 2013) - Stein, Stacey M.; Tiersten, Amy; Hochster, Howard S.; Blank, Stephanie V.; Pothuri, Bhavana; Curtin, John; Shapira, Ilan; Levinson, Benjamin; Ivy, Percy; Joseph, Benson; Guddati, Achuta Kumar; Muggia, Franco
Abstract : Background: Phase 2 trials suggest that prolonged intravenous (IV) infusion of the topoisomerase 1 inhibitor topotecan may be less toxic than when given by standard IV bolus 5-day administration. Oxaliplatin exhibits efficacy in platinum-pretreated disease and shows preclinical synergy with topoisomerase 1 inhibitors. We sought to determine the efficacy and safety of oxaliplatin plus infusion topotecan in recurrent platinum-pretreated ovarian cancer. Methods: Patients with recurrent epithelial ovarian, fallopian tube, or primary peritoneal cancers previously treated with 1 to 2 prior regimens including platinum and taxane received oxaliplatin (85 mg/m 2 day 1 and day 15) and topotecan (0.4 mg/m 2 per day) by continuous IV infusion over 14 days every 4 weeks. The primary objective of the trial was to estimate the objective response rate in platinum-resistant disease (stratum 1) and in platinum-sensitive disease (stratum 2). Toxicities were assessed in all patients. Results: Thirty-eight patients received 144 cycles of therapy (median, 4; range, 1–6). The most common grade 3 and grade 4 toxicities included thrombocytopenia (grade 3, 37%; and grade 4, 19%), neutropenia (grade 3, 37%; grade 4, 11%), and anemia (grade 3, 15%). Response occurred in 4 of 19 patients in stratum I (21%; 95% confidence intervals, 6%–46%) and 9 of 19 patients in stratum 2 (47%; 95% CI, 24%–71%). Three in each stratum had lengthy complete responses. Conclusions: Biweekly oxaliplatin plus a 14-day continuous IV infusion of topotecan, given monthly, is an active regimen in platinum-pretreated ovarian cancer and merits additional evaluation.